Measuring Democratization and Detecting State Transitions - Papanikolaou, Vaia; Roussakis, Yiannis; Tzionas, Panagiotis (HAPSc Policy Briefs Series, 2020)
In the proposed research, an in-depth analysis of the features presented in six representative international organizations measuring democracy worldwide revealed a sizeable set of significant and complementary indicators that provided the basis for the construction of a common conceptual framework for democratization. The size and variety of the examined datasets overcomes any possible skepticism for data biasing. We also propose a method of combining such complementary or competing indicators using Multi-objective Optimization, in order to increase objectivity. The periodic monitoring of the proposed indicators allows for the detection of State Transitions, especially under alarming conditions. Our aim is to propose an objective tool for policy makers that would eliminate selective interpretation of democracy and its transitions, by allowing political change to be meaningfully understood in its proper perspective using facts and data.